Pengaruh Pengendalian Internal Terhadap Pelaporan Keuangan Yang Berkualitas (Penelitian Pada Hotel Berbintang Di Kota Bandung) - Antonius Bimo Rentor (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
It is difficult to find a financial statement which meet the criteria of characteristic of qualitative accounting information. This might caused by several factors. One of the factor that can be analyze related to the existance of correlation to quality financial reporting is internal control. This research purpose is to analyze this existance of correlation between internal control using COSO internal control framework with quality financial reporting. Research analysis method used is partial least square with starred hotel in Bandung as its population. The sampling technique used is stratified random sampling. The result of this research shows that implementation of internal control using COSO IC framework has no correlation with quality financial reporting especially in hotel industry. This represent a situation that hotel industry are more focusing their strategy by analyzing the risk perspective rather than focusing on the control process.